2023
DOI: 10.1108/jcp-01-2023-0004
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the complexities of non-familial child abductions: a systematic literature review on the behavioural characteristics of acquaintance and stranger abductors

Abstract: Purpose Reports from 2016 to 2017 suggest that approximately 870 cases of non-familial child abduction (NFA) are recorded in England and Wales per year. Yet, empirical knowledge of the victims, offenders and offence characteristics is limited in comparison to other forms of child victimisation. Furthermore, much of the available knowledge is constrained by a lack of clarity around the differences between acquaintance and stranger abductors. This systematic literature review aims to develop a comprehensive over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…There has been a huge push in recent years within the CJS towards victim-oriented policy and procedures (Fielding 2013;Smith et al 2022). Yet, despite institutional agreement, there exists key divides within the general public's perceptions of victims (Lilley et al 2023b;Stevens et al 2024), defendants (Chesser et al 2023;Lewandowicz-Machnikowska et al 2023), and the appropriate treatment of both (Jones et al 2023;Sowersby et al 2022;Williams et al 2023). The current research, in line with previous findings, found that the British public demonstrates victim-oriented attitudes, as a higher proportion of respondents rated the court's ability to help victims as poor than rated the protection of the accused as poor (Kaukinen and Colavecchia 1999).…”
Section: Perceptions Of Victim Treatmentmentioning
confidence: 99%
“…There has been a huge push in recent years within the CJS towards victim-oriented policy and procedures (Fielding 2013;Smith et al 2022). Yet, despite institutional agreement, there exists key divides within the general public's perceptions of victims (Lilley et al 2023b;Stevens et al 2024), defendants (Chesser et al 2023;Lewandowicz-Machnikowska et al 2023), and the appropriate treatment of both (Jones et al 2023;Sowersby et al 2022;Williams et al 2023). The current research, in line with previous findings, found that the British public demonstrates victim-oriented attitudes, as a higher proportion of respondents rated the court's ability to help victims as poor than rated the protection of the accused as poor (Kaukinen and Colavecchia 1999).…”
Section: Perceptions Of Victim Treatmentmentioning
confidence: 99%